2010
DOI: 10.1073/pnas.1015163108
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of synaptic stability by AMPA receptor reverse signaling

Abstract: The establishment of neuronal circuits relies on the stabilization of functionally appropriate connections and the elimination of inappropriate ones. Here we report that postsynaptic AMPA receptors play a critical role in regulating the stability of glutamatergic synapses. Removal of surface AMPA receptors leads to a decrease in the number and stability of excitatory presynaptic inputs, whereas overexpression increases synapse number and stability. Furthermore, overexpression of AMPA receptors along with Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Postsynaptic Ca 2þ is, in turn, necessary for LTF, perhaps through retrograde signaling to presynaptic ApCAM, neurexin, or Trk receptors (Purcell et al 2003;Ormond et al 2004;Sharma et al 2006;Cai et al 2008;Hu et al 2010;Choi et al 2011;Kassabov et al 2013). The new postsynaptic clusters of AMPA-like receptors may also participate in retrograde signaling, and recruit presynaptic clusters of synaptophysin during a later stage of ITF and growth of presynaptic varicosities during LTF (Kim et al 2003;Ripley et al 2011;Lee et al 2012). These ideas are similar to theoretical "cascade" models of memory storage that can show plasticity as well as long-term stability (Fusi et al 2005), which would seem to be mutually exclusive but are both essential features of memory.…”
Section: Possible Relationships Between Mechanisms Contributing To Stmentioning
confidence: 55%
“…Postsynaptic Ca 2þ is, in turn, necessary for LTF, perhaps through retrograde signaling to presynaptic ApCAM, neurexin, or Trk receptors (Purcell et al 2003;Ormond et al 2004;Sharma et al 2006;Cai et al 2008;Hu et al 2010;Choi et al 2011;Kassabov et al 2013). The new postsynaptic clusters of AMPA-like receptors may also participate in retrograde signaling, and recruit presynaptic clusters of synaptophysin during a later stage of ITF and growth of presynaptic varicosities during LTF (Kim et al 2003;Ripley et al 2011;Lee et al 2012). These ideas are similar to theoretical "cascade" models of memory storage that can show plasticity as well as long-term stability (Fusi et al 2005), which would seem to be mutually exclusive but are both essential features of memory.…”
Section: Possible Relationships Between Mechanisms Contributing To Stmentioning
confidence: 55%
“…Finally, one important mechanism through which synapse stability could be improved is by changes in the organization of the postsynaptic density (PSD) that promote trans-synaptic adhesion and contact. Expression of PSD95 and/or AMPA receptors enhances synaptic strength and synapse stability 28,29 . Several adhesion molecule systems have also been linked to spine stability, including neuroligin 1 (REFS 29,30) and N-cadherin.…”
Section: Spine Dynamicsmentioning
confidence: 99%
“…The observation that the amount of GluR1 does not correlate with presynaptic strength, whereas the amount of NMDA receptors and PSD-95 does, suggests that not all postsynaptic proteins are affected by retrograde signaling that matches preand postsynaptic properties. Recent studies showed that the amount of AMPA receptors does not correlate with presynaptic strength with baseline activity (Tokuoka and Goda 2008), and AMPA receptor subunits retrogradely stabilize presynaptic terminals when neuroligin-1 is present (Ripley et al 2010). Our work suggests that the amount of two postsynaptic proteins, NMDA receptors and PSD-95, is an indirect indicator of presynaptic strength, regardless of the spatial configuration or the identity of postsynaptic neuron targets.…”
Section: Discussionmentioning
confidence: 74%